Best of Both Worlds? The Potentials and Challenges of Implementing Sustainable and Smart Urban Mobility - Schröder, Carolin (Frontiers in Sustainable Cities, 2022)
In recent years, many academic and technical discussions about cities have been shaped by two topics: sustainability and smartness. While these two areas are evolving, there are definitely common grounds to be found in discourses on sustainability and smartness. First of all, this is the realization that any comprehensive transformation of long-term, complex processes requires governance and integration of topics and institutions, and second, that there can be no uniform approach to successfully becoming more sustainable or smarter. However, different directions of development can be identified that may – or may not – go together. Urban mobility has to deal with different definitions of and approaches to sustainability and smartness too. A specific format developed during the transdisciplinary project ‘Neue Mobilität Berlin’ (New Mobility Berlin, http://neue-mobilitaet.berlin/) addresses these questions. Research results suggest, for one, that there are very practical technical issues that complicate a transition from existing mobility systems towards more sustainable and smart ones. For another, the results suggest that a comprehensive sustainable and smart urban mobility system will need more integration and coordination. This contribution takes off from project findings and discusses implications for the implementations of and discourses on smart and sustainable urban mobility.